The Use of Alternative Data by Fintechs to Provide Access to Credit for SMEs in South Africa - Khupe, Mandlenkosi M. (University of the Witwatersrand, Johannesburg, 2024)
In South Africa, access to finance remains one of the major contributors to SME failures. The International Finance Corporation estimates that the credit gap for MSMEs in South Africa is R510bn. Traditional lenders often impose stringent requirements and avoid certain segments due to high information asymmetry costs. This factor has led to the advent of fintechs that seek innovative ways to provide unsecured funding. This study examines the role of fintechs in leveraging alternative data to provide credit access to SMEs. The study adopts a standard qualitative approach, with the primary methodology used to collect data being semi-structured interviews. Thirteen participants with varied exposure to alternative data in the fintech sector were interviewed. The findings of the study reveal the transformative nature of alternative data, as it significantly reduces information asymmetry and enhances credit provision. Furthermore, the study concludes that alternative data should be used to supplement rather than replace traditional data. The research highlights the fact that while fintechs favour hard data over soft data for more objective decision-making, the use of alternative data in South Africa is still emerging. The study further reveals that soft data are less weighted by fintechs compared to hard data which enable fintechs to make objective decisions. The conclusion reached is the need for collaboration among fintechs, regulators, and other stakeholders in the financial ecosystem to foster and promote data sharing practices in the alternative data space. This collaborative approach is essential for addressing the prevailing issues of information asymmetry and for further enhancing SME access to finance.
A research report submitted in fulfillment of the requirements for the Master of Management in the field of Digital Business, In the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Lending; SMME; Alternative data; SDG-8: Decent work and economic growth